“ANKER” Video Prosedur K3 untuk Meningkatkan Kesadaran Kerja di Laboratorium Mikrobiologi - Putra, Renardi Erwinsyah; Hofifah, Siti Nur; Maemunah, Iin; Purwanti, Sri Tri; Barmana, Doni (Jurnal Pengelolaan Laboratorium Pendidikan, 2024)
This research aims to examine the production of occupational health safety (OHS) videos in microbiology laboratories. The procedure used is "ANKER", which is an acronym for work analysis and reconstruction from making OHS videos used in workshop activities to increase work awareness in the microbiology laboratory. The OHS video analysis score using the VEE diagram obtained 38 points on a scale of 100. The work procedure was carried out by testing the OHS video with 37 workshop participants. On the basis of obtaining the scores above, video reconstruction needs to be carried out which includes adding Focus Questions, clarifying knowledge claims, adding data recording processes and activities. The results of interviews with respondents showed an incompatibility between the music and the storyline so that the background music in the video needed to be replaced. After the reconstruction process using the VEE diagram, a score of 94 points on a scale of 100 was obtained. Thus, the use of the "ANKER" procedure using the VEE diagram can be used to increase awareness of working in a microbiology laboratory. Respondents were of the opinion that K3 information via video was very helpful in increasing awareness of working in the laboratory. Submission of information about K3 must be carried out before carrying out laboratory activities and after carrying out laboratory activities as part of the practical evaluation